Gender discrimination and deprivation: current situation and prospects for alleviation - Ocampo, Perla D. Santos (The Turkish Journal of Pediatrics, 1998)
Worldwide, there is a tremendous concern towards violence against the girl-child. The title of this paper is broader and may connote a discrimination against either sex. However, it is recognized that gender discrimination usually means violence against women and girls. I will start with specific issues which are good indicators of the plight of many girl-children in the world.